Simulation research on ultrasonic guided waves detection of metal rod buffer system bonding quality - Yang Hu; Wang Cheng (Institute of Advanced Engineering and Science, 2013)
The judgment of metal rod buffer system bonding quality depends on the bond of the metal rods with the surrounding medium. System bonding area will lead to different reflection amplitude. Compared the simulation with the experiment, it can be concluded that different bonding area can measure bond quality, i.e, the greater the bonding area is the more excellent bonding quality will be. This conclusion provides the basis for the system ultrasonic testing. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2193